Meningkatkan Pemahaman Matematika melalui Integrasi Problem Based Learning (PBL) dan Experiential Learning: Studi Kasus Kelas 7G SMPN 4 Madiun - Purdiana, Roro Agnes; Murtafiah, Wasilatul; Hartono, Henry Yuli (Wacana Akademika: Majalah Ilmiah Kependidikan, 2024)
This study explores the effectiveness of combining Problem Based Learning (PBL) and Experiential Learning in enhancing students' understanding of mathematical concepts, specifically the volume of solid figures, in the 7G class of SMPN 4 Madiun. The research was conducted over two cycles. The first cycle implemented PBL, while the second cycle integrated PBL with experiential learning. The research method employed was classroom action research using both quantitative and qualitative approaches. Data were collected through learning outcome tests and participatory observations. Qualitative descriptive analysis was conducted to identify patterns of interaction and student responses during the learning process. The findings indicated that students were more active in discussions, used visual aids effectively, and overcame difficulties in understanding mathematical concepts in the second cycle. Quantitative analysis using paired sample t-test showed a significant improvement in understanding mathematical concepts in the second cycle (). The conclusion confirms that integrating PBL with experiential learning effectively enhances student engagement and comprehension of mathematical concepts.